O-032 Initial implementation of dual-energy CT for post-procedure imaging after mechanical thrombectomy at a single institution. (22nd July 2018) - Magarik, J; Chitale, R; Fusco, M; Froehler, M; Aulino, J; Davis, L
Abstract : Background: Post-procedure intracranial imaging is important to help guide blood pressure management, and the potential need for anti-platelet therapy in post-thrombectomy patients. However, discerning contrast staining from acute hemorrhage in post-thrombectomy patients can be difficult as both entities appear hyperdense on non-contrast head CT. Newer imaging modalities such as dual-energy (DE) head CT may provide a viable solution by separating blood from iodine during CT acquisition. We describe our initial experience of implementing DE head CT in post-thrombectomy patients at a single institution. Methods: Post-thrombectomy patients who underwent post-surgical DECT head imaging were evaluated from October 2017-January 2018 (since implementation of DE imaging) at our institution. Two independent neuroradiologists blindly reviewed the post-thrombectomy DECT head for hemorrhage and the subsequent post-operative MRI, both of which were performed within 24 hours of intervention. When MRI could not be performed, a follow-up standard head CT was performed at 24 hours. Sensitivity, specificity, positive predictive value and kappa values for inter-observer variability were calculated. Data on age, gender, NIHSS, modified TICI score, number of thrombectomy attempts (aspiration, stent retriever, or both) and 90 day modified Rankin score (mRS) were collected, as well. Results: Twenty-three patients were evaluated with post-thrombectomy DECT head imaging. Post-thrombectomy MRI was performed in 18/23 patients (78%). Mean age, presenting NIHSS score, percent TICI 2b or greater revascularization was 64, 14, and 91%, respectively. Mean number of thrombectomy attempts was 1.7. Ninety-day mRS was available in 17/23 patients (74%) and 59% of patients achieved mRS≤2 at 90 days. Sensitivity, specificity, and positive predictive value (PPV) of identifying hemorrhage on the DECT by neuroradiology reader A was: 57.1%, 89.0%, and 89.0%, respectively. In neuroradiology reader B they were: 58.0%, 73.0%, and 70.0%, respectively. The kappa value between readers was 0.7. Conclusion: In our initial implementation of DECT imaging in post-thrombectomy patients, there is substantial inter-observer agreement between two neuroradiologists. While the patient cohort is small, the high PPV of DECT imaging can aid in the post-operative management of these patients. It can also help in the decision and timing to start anti-platelet therapy. Importantly, the high specificity of DECT indicates that this technique can serve as a useful discriminator between clinically-insignificant contrast staining and actual intracerebral hemorrhage. Disclosures: J. Magarik: None. R. Chitale: None. M. Fusco: None. M. Froehler: None. J. Aulino: None. L. Davis: None.